Antiviral activity of extracellular vesicles derived from respiratory syncytial virus-infected airway epithelial cells - Corsello, Tiziana; Qu, Yue; Ivanciuc, Teodora; Garofalo, Roberto P.; Casola, Antonella (Frontiers in Immunology, 2022)
Respiratory syncytial virus (RSV) is a major cause of acute lower respiratory tract infections in children and elderly. No vaccine or effective treatment is currently available for RSV. Extracellular vesicles (EVs) are microvesicles known to carry biologically active molecules, including RNA, DNA and proteins (i.e. cargo). Viral infections can induce profound changes in EV cargo, and the cargo can modulate cellular responses of recipient cells. We have recently shown that EVs isolated from RSV-infected cells were able to activate innate immune response by inducing cytokine and chemokine release from human monocytes and airway epithelial cells, however, we did not investigate the potential antiviral contribution of EVs to a subsequent infection. The objective of this study was to assess the presence of innate immune mediators, including type I and III interferons (IFNs) in EVs released from airway epithelial cells infected with RSV, and their potential role in modulating viral replication in recipient cells. EV-derived from cells infected with RSV were associated with significant amounts of cytokine and chemokines, as well as IFN-β and -λ, compared to EVs isolated from mock-infected cells. Cells treated with RSV-EVs showed significantly lower levels of viral replication compared to untreated or mock-EV-treated RSV infected cells. Cellular pretreatment with Cerdulatinib, an IFN receptor signaling inhibitor, inhibited the antiviral activity of RSV-EVs in recipient airway epithelial cells. Furthermore, treatment of A549 cells with RSV-EVs induced the expression of IFN-dependent antiviral genes, supporting the idea that RSV-EVs exerts their antiviral activity through an interferon-dependent mechanism. Finally, we determined the concentrations of soluble and EV-associated IFN-β and IFN-λ in five nasopharyngeal secretions (NPS) of children with viral infections. There were significant levels of IFN-λ in NPS and NPS-derived EVs, while IFN-β was not detected in either of the two types of samples. EVs released from RSV-infected cells could represent a potential therapeutic approach for modulating RSV replication in the airways.